AFFECTING FACTORS AND THE ROLE OF TAX AUDIT IN INDONESIA - Hartanto, Anton Dwi; Rahmiati, Alfa (Jurnal Aplikasi Akuntansi, 2025)
The Directorate General of Taxation (DGT) conducts tax audits as a control measure for the self-assessment system in Indonesian taxation. The abundance of articles on tax audits in Indonesia encourages writers to thoroughly examine the literature from journals specializing in accounting and taxation. This research aims to analyze the factors that affect tax audits and the role of tax audits in Indonesia. The findings show that the information system, the competence of tax auditors, the independence of tax auditors, and tax audit policies affect tax audits. Tax audits play a role in tax compliance and tax revenue. It is anticipated that this research will help the DGT enhance the variables influencing tax audits and raise the quality of these audits.